2021
DOI: 10.1093/inthealth/ihaa106
|View full text |Cite
|
Sign up to set email alerts
|

The male disadvantage in life expectancy: can we close the gender gap?

Abstract: Men are usually considered to be the stronger sex. However, when it comes to health, they are evidently weaker than their female counterparts. In almost all countries around the world, men consistently live shorter lives than women. The gender gap in longevity has once again been evident during the ongoing coronavirus disease 2019 (COVID-19) pandemic, which kills men disproportionately. Drawing on the relevant scientific literature and updated information, this article aimed to provide useful insights into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…In other words: health inequity (measured by life expectancy at district level) in contemporary Germany crystallizes quite clearly when life expectancy is operationalized as remaining life expectancy at older ages. Thus it comes to no surprise at all that the well-known 'gender gap in life expectancy' [84][85][86][87] can also be found when regarding remaining life expectancy at older ages.…”
Section: Analyzing Potential Predictors Of Men's and Women's Remaining Life Expectancy At Age 60 Using Multivariate Regression Analysesmentioning
confidence: 99%
“…In other words: health inequity (measured by life expectancy at district level) in contemporary Germany crystallizes quite clearly when life expectancy is operationalized as remaining life expectancy at older ages. Thus it comes to no surprise at all that the well-known 'gender gap in life expectancy' [84][85][86][87] can also be found when regarding remaining life expectancy at older ages.…”
Section: Analyzing Potential Predictors Of Men's and Women's Remaining Life Expectancy At Age 60 Using Multivariate Regression Analysesmentioning
confidence: 99%
“…Both are associated with a higher risk of neonatal mortality and many other problems, such as feeding difficulties and delayed milestones. 14 Receipt of antenatal care is integral to the wellbeing of a foetus, 16,17,18 and our study showed that neonates whose mothers did not receive any ante-natal care were a slightly increased risk of death (OR: 1.61 [95% Cl 1.01-2.57]). Tietzmann et al noted a similar relationship between the number of antenatal visits and neonatal mortality, noting that mothers who had less than four antenatal visits had a higher incidence of neonatal mortality, (OR: 1.21 [95% Cl 1.05-1.40)].…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies also reported differences in cognitive function between males and females [ 13 , 51 ]. Genetic variations between females and males, as well as gender variations in the pattern of lifestyle behaviors, are potential causes of such differences [ 52 ]. We further investigated the “dietary–smoking–gender” three-way interaction effects of each food separately, and we found that “meat” and “fish or seafood” contributed most to the gender variations in interactions between smoking in the past and dietary diversity with respect to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%